Age, Growth, and Validation of Otolith Morphometrics as Predictors of Age in the Blackspot Seabream, Pagellus bogaraveo, (Brunnich, 1768) from the Eastern Adriatic Sea - Antonela Paladin; Nika Ugrin; Sanja Matić-Skoko; Branko Dragičević; Jakov Dulčić (Fishes, 2023)
The age and growth of the blackspot seabream, Pagellus bogaraveo, were determined by examining sagittal otoliths from fish sampled in the eastern Adriatic Sea. A total of 674 specimens (181 males, 90 hermaphrodites, 108 females, and 295 immatures) ranging from 8.80 to 47.27 cm (21.93 ± 9.00 cm) in total length were analyzed. The maximum observed age for the whole sample was 13 years. The sample was dominated by 1-year-old specimens as a consequence of an abundance of juvenile specimens collected by beach seines. Growth was described by the von Bertalanffy growth curve (L∞ = 52.3 cm, K = 0.15 year−1, t0 = 0.49 year, R2 = 0.97), and the growth performance index (Φ’) was 2.61. The length, width, thickness, and mass of the otoliths were compared with the total length and age of P. bogaraveo from the eastern Adriatic. The analysis showed that the measures were adequate predictors of age. These results can be of value for more effective management measures aimed at the conservation of this species.